(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
This study aims to investigate the aqueous extract of Sophora japonica pods for the presence of various phytochemicals and to synthesize sulfur nanoparticles. The presence of various phytochemicals viz. polyphenols, alkaloids, terpenoids, flavonoids, and tannins were investigated by standard biochemical methods.Â A rapid, green and novel approach for synthesis sulfur nanoparticles (SNPs) from sodium thiosulfate in the presence of Sophora japonica pods aqueous extract in one-pot reaction at ambient temperature. The resulting sulfur nanoparticles were characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results show that sulfur nanoparticles were successfully synthesized in sphere shape, and with an average particle size 5-100 nm. The effect of plant pods extract concentration on particle size of sulfur nanoparticles shows that can significantly reduce the particle size without changing the shape. The results revealed that the aqueous extract of Sophora japonica pods act as capping, dispersing and stabilizing agent for sulfur nanoparticles. This method is a novel approach for production nanosized sulfur particles, which could be applied to prepare sulfur nanoparticles for application in antimicrobial activity, fertilizers, and plant protection.